Consumer Behavior Analysis of MSME Products through Social Media Interaction during Eid al-Fitr Celebration - Purnomo, Yudiyanto Joko (PT. LITERASI SAINS NUSANTARA, 2024)
Eid al-Fitr celebration is a significant moment in the culture and tradition of Muslim society, where the consumption of goods and services increases significantly. During this period, consumers tend to be more open to purchasing products related to the celebration's needs, such as clothing, food, and home decorations. This research aims to delve deeper into how consumer behavior towards MSME products during Eid al-Fitr celebration is influenced by social media interaction. The research method employed is a literature review with a qualitative approach utilizing descriptive analysis. Data used were gathered from academic sources indexed in Google Scholar, spanning from 2015 to 2024. The study's results indicate that in the current digital era, social media interaction plays a crucial role in influencing consumer behavior, especially during Eid al-Fitr celebration. MSMEs have significant opportunities to leverage social media to enhance product visibility and influence consumer purchasing decisions. Consumer behavior analysis suggests that factors such as content type, posting frequency, user interaction, and visual content quality greatly affect consumer interest. Moreover, brand trust and credibility also play a key role in influencing consumer behavior. Interaction between consumers and brands through comments, testimonials, or product reviews also has a significant impact on purchasing decisions. External factors such as market trends, economic conditions, and government policies also influence consumer behavior, necessitating MSMEs to have flexibility in adapting their marketing strategies.